The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.neuroimage.2019.03.068
|View full text |Cite
|
Sign up to set email alerts
|

Multi-branch convolutional neural network for multiple sclerosis lesion segmentation

Abstract: In this paper, we present an automated approach for segmenting multiple sclerosis (MS) lesions from multi-modal brain magnetic resonance images. Our method is based on a deep end-to-end 2D convolutional neural network (CNN) for slice-based segmentation of 3D volumetric data. The proposed CNN includes a multi-branch downsampling path, which enables the network to encode information from multiple modalities separately. Multi-scale feature fusion blocks are proposed to combine feature maps from different modaliti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
111
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(113 citation statements)
references
References 49 publications
2
111
0
Order By: Relevance
“…For comparison, we evaluated two state-of-the-art MS WML segmentation methods publicly available: LST-LGA is an unsupervised lesion growth algorithm ( Schmidt et al, 2012 ) implemented in the LST toolbox version 3.0.0 ( LST, 2020 ) for Statistical Parametric Mapping (SPM). LST-LGA has been widely evaluated in the context of MS WML segmentation and used as comparison with more recent approaches ( Aslani et al, 2019 , Valverde et al, 2017 , Roy et al, 2018 ). In a nutshell, the algorithm performs an initial bias field correction and affine registration of the T1 image (in our case the MP2RAGE) to the FLAIR, and then proceed with the lesion segmentation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For comparison, we evaluated two state-of-the-art MS WML segmentation methods publicly available: LST-LGA is an unsupervised lesion growth algorithm ( Schmidt et al, 2012 ) implemented in the LST toolbox version 3.0.0 ( LST, 2020 ) for Statistical Parametric Mapping (SPM). LST-LGA has been widely evaluated in the context of MS WML segmentation and used as comparison with more recent approaches ( Aslani et al, 2019 , Valverde et al, 2017 , Roy et al, 2018 ). In a nutshell, the algorithm performs an initial bias field correction and affine registration of the T1 image (in our case the MP2RAGE) to the FLAIR, and then proceed with the lesion segmentation.…”
Section: Methodsmentioning
confidence: 99%
“… nicMSlesions is a state-of-the-art deep learning WML segmentation method ( Valverde et al, 2017 , Valverde et al, 2019 ). Having reached an excellent performance in a MS lesion segmentation challenge ( Carass et al, 2017 ), it is now a common method to compare with ( Aslani et al, 2019 , Weeda et al, 2019 , Roy et al, 2018 ). This method selects lesion candidates’ voxels based on the FLAIR contrast and extracts 11x11x11 patches around them.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aslani et al [27] introduced an automated method for segmenting MS lesions from multi-modal brain magnetic resonance images. Their approach based on a deep-end to end 2D CNN.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[15][16][17] But as taking 3D context information into consideration, 3D methods can maintain the 3D consistency between the segmentation of different slices and should be theoretically more consistent and accurate than 2D methods. However, in the context of cardiac image segmentation, due to the low through-plane resolution characteristic of cardiac MRI and the shortcomings of 3D methods such as reduction of training images and high risk of overfitting, 15,18 the segmentation performance of 3D methods may be limited to some extent. For instance, the previous work [19][20][21] evaluated on the automatic cardiac diagnosis challenge (ACDC) dataset indicated that the proposed 3D models did not meet the expectations in performance improvement over the corresponding 2D models.…”
Section: Introductionmentioning
confidence: 99%